DYNAMIC TESTING OF BRIDGES WITH IMPULSE LOADING - Serhii Zavhorodniy; Vasyl Redchenko (Дороги і мости, 2023)
Introduction. This article deals with the practice of applying the method of dynamic testing of bridges, namely, modal control using impulse loading. The possibilities of this method for determining the technical condition of a bridge span structure by determining its natural characteristics: actual stiffness and parameters of natural vibration forms are shown.